Diallel analysis in sorghum for forage yield and attributes by Griffing and Hayman’s approaches - R. A. Gami*1, K. G. Kugashiya1 , R. S. Solanki2 and R. N. Patel3 (Electronic Journal of Plant Breeding, 2023)
Five sorghum (Sorghum bicolor (L.) genotypes were crossed in a half-diallel mating design. Analysis of variance for combining ability revealed that general combining ability (GCA) was significant for all the traits except days to flowering, while specific combining ability was significant for all the studied traits. The variance ratio (δ2 GCA / δ2 SCA) was less than unity for all characteristics, demonstrating the role of non-additive gene action in controlling yield and component traits. The result of general combining ability (GCA) indicated that the parents SH 1488 and SH 1813 were as good general combiners for both green and dry fodder yield per plant. Result of specific combining ability (SCA) showed that crosses SSG 59 × SH 1488, SH 1488 × SH 1813, SH 1488 × S 652 and SH 1811 × S 652 recorded the highest sca effect for the traits green and dry fodder yield per plant. The t2 test specified the fulfilment of the assumption required under diallel analysis for all studied traits except leaf length (cm) and green fodder yield per plant (g). Nonsignificant result of t2 value suggested additive dominance model for all the traits except leaf length (cm) and green fodder yield per plant (g). The higher value of H1 compared to H2 for most of the characters suggested that gene sharing frequency in parent genotypes was not equal and that was also supported by the H2 / 4H1 (<0.25). The greater than one value of KD/KR components for most of the traits except leaf width (cm) and HCN content (ppm) suggested the higher frequency of dominant genes than recessive genes in the parents. The estimation of the F component was positive and non-significant for all the traits except leaf width (cm), whose value was negative. In Hayman’s graphical analysis, the regression line interrupted Wr axis below the origin suggested over dominance for days to flowering, leaf: stem ratio, number of leaves per plant, stem girth and Brix content.